Efficacy of nebulized hypertonic saline versus normal saline in the treatment of acute bronchiolitis in inpatient infants - Ganimeta Bakalović; Tarik Jarkoč; Nedim Begić; Orhan Lepara; Dejan Bokonjić; Dušan Mihajlović; Amela Pasić; Almir Fajkić (Medicinski glasnik, 2023)
Aim: Compare the efficacy of nebulized hypertonic saline and normal saline in the treatment of infants hospitalized for bronchiolitis. Methods: This retrospective study was conducted at the Department of Pulmonology, Paediatric Clinic, Clinical Centre University of Sarajevo, covering the period from January 2015 to December 2019 and comprising 380 children aged between 1 and 12 months having bronchiolitis. One group received nebulized hypertonic saline (NHS, 3% NaCl)), and another group received nebulized normal saline (NNS, 0.9% NaCl). The control group did not receive any of these treatment options. Results: There was no statistically significant difference between the treatment groups regarding length of hospital stay (LOS) and Clinical Severity Score (CSS) at admission and discharge as well as in oxygen therapy duration and antibiotic use, the duration of symptoms before hospital admission, frequency of nasal discharge, elevated temperature, dyspnoea, cough and dehydration. Conclusion: The results of this study are consistent with several recent studies or meta-analyses and support the evidence against the use of NHS in hospitalized infants with mild or moderate bronchiolitis.
Keywords: bronchioles; infection; therapy; NaCl